Transpiration efficiency in the major races of Ethiopian sorghum: Unraveling genetic variation for drought adaptation - Mitiku, Abel Debebe; Feyissa, Tileye; Woldetensaye, Alemu Tirfessa; Chikssa, Habte Nida; Menamo, Temesgen Matiwos; Abebe, Tewodros Mesfin; Bante, Kassahun (Informa UK Limited, 2025)
Sorghum is a crucial cereal crop, recognized for its resilience to arid and semiarid environments. However, drought stress significantly limits its productivity, emphasizing the need to enhance drought tolerance traits. One such trait is transpiration efficiency (TE), which reflects a plant’s ability to use water efficiently. This study tested a core collection of 182 Ethiopian sorghum accessions, representing major races for drought tolerance related traits. The accessions were grown in 16 l lysimeters under a rain-out shelter, employing a randomized complete block design with three replications. Our findings revealed significant genetic variation (p < 0.001) in TE and related traits among sorghum races. Durra races exhibited the highest TE (6–8.5 kg/L), while intermediate races (dura-caudatum, kafir-caudatum, dura-guinea) showed moderate. Conversely, kafir-caudatum, kafir-bicolor, guinea-bicolor, guinea-caudatum, dura-caudatum and bicolor exhibited the lowest TE. Strong correlations were found between TE and traits such as total shoot fresh weight, total shoot dry weight, and leaf number. Principal component analysis identified key traits influencing TE, while cluster analysis grouped accessions into four distinct clusters, with Cluster IV containing genotypes with the highest TE. These findings highlight the potential of TE in breeding water-efficient sorghum varieties and provide valuable genetic resources for enhancing drought tolerance.